Antibiotics: mechanisms of action - Anca Marculescu (Medicamentul Veterinar)
The antibiotics are a very important class of chemotherapeutic agents that are capable to stop or even selectively destroy pathogens in man and animal. Antimicrobial agents affect susceptible organisms in various ways. The major mechanisms of action of antibiotics are: inhibition of cell wall synthesis, impairment of cell membrane function, inhibition of protein synthesis, inhibition of nucleic acids synthesis.